Seed morphometry of Rheum L. (Polygonaceae) species from Kazakhstan and its implications in taxonomy and species identification - AIDAR A. SUMBEMBAYEV; OLGA A. LAGUS; SŁAWOMIR NOWAK (Society for Indonesian Biodiversity, 2023)
Abstract. Sumbembayev AA, Lagus OA, Nowak S. 2023. Seed morphometry of Rheum L. (Polygonaceae) species from Kazakhstan and its implications in taxonomy and species identification. Biodiversitas 24: 4677-4692. In the article, the evaluation of morphometric and weight parameters of seeds of 7 species of the genus Rheum L. from Kazakhstan is presented, as well as an analysis of their biometric parameters from different ecological and geographical habitats. The purpose of the study was to determine the variability of the seeds of the studied taxa and the importance of the results in determining the taxonomic relationships within the genus. The external structure was described for all species of the genus. Seeds of all studied species are illustrated with photos and scale drawings, and their features are summarized in a table. Stable and taxonomically significant features were identified for the species of the section Ribesiformia, represented by R. cordatum and R. maximowiczii, allowing their identification. The correlation between seed metric parameters and environmental conditions of the site and growth area was established and found a significant relationship between morphometric data and most of the environmental factors studied. The low adaptive potential of rhubarb species in Kazakhstan and the species' narrow ecological range were found. The comparison of the results obtained with the taxonomic relationships and phylogeny of representatives of the genus are briefly discussed.